2021
DOI: 10.1002/smll.202007775
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐in‐Polymer Templating for Fabrication of Carbon Nanofibers with Controlled Interior Substructures: Designing Versatile Materials for Energy Applications

Abstract: A simple, scalable, surfactant‐in‐polymer templating approach is demonstrated to create controlled long‐range secondary substructures in a primary structure. A metal bis(2‐ethylhexyl) sulfosuccinate (MAOT) as the surfactant is shown to be capable of serving as a sacrificial template and metal precursor in carbon nanofibers. The low interfacial tension and controllable dimensions of the MAOT are maintained in the solid‐phase polymer, even during electrospinning and heat‐treatment processes, allowing for the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…29 Three representative ICNFs were prepared from the precursor combinations of PAN/PMMA, PAN/PVP, and PAN/PMMA/PVP with iron(II) acetate as an iron precursor; these materials were labeled ICNF-1, ICNF-2, and ICNF-3, respectively. 30,31 Figure 1 shows the surface morphologies and interiors of the ICNFs obtained from the different polymer precursor combinations, where it was found that the diameter and morphology of the nanofibers were dependent on the polymer precursors. While the nanofibers in ICNF-1 and ICNF-3 were twisted and bent, those in ICNF-2 were straight.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Three representative ICNFs were prepared from the precursor combinations of PAN/PMMA, PAN/PVP, and PAN/PMMA/PVP with iron(II) acetate as an iron precursor; these materials were labeled ICNF-1, ICNF-2, and ICNF-3, respectively. 30,31 Figure 1 shows the surface morphologies and interiors of the ICNFs obtained from the different polymer precursor combinations, where it was found that the diameter and morphology of the nanofibers were dependent on the polymer precursors. While the nanofibers in ICNF-1 and ICNF-3 were twisted and bent, those in ICNF-2 were straight.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, iron precursor ions can coordinate to the lactam group of PVP. , Therefore, a rational combination of polymers as carbon precursors allows for the control of not only the major textural properties of the carbonized product but also the incorporation and formation (size and distribution) of the iron phase formed on/in the carbonized product, which is subsequently heat-treated to produce the desired ICNFs . Three representative ICNFs were prepared from the precursor combinations of PAN/PMMA, PAN/PVP, and PAN/PMMA/PVP with iron­(II) acetate as an iron precursor; these materials were labeled ICNF-1, ICNF-2, and ICNF-3, respectively. , …”
Section: Resultsmentioning
confidence: 99%
“…202300217 properties in the nanometer regime may allow for the creation of nanohybrids with properties distinct from those of their constituents. [3] Furthermore, in the process of creating nanohybrids, the usual synthetic variables as well as additional material variables can be considered, [4,5] which open up possibilities for exploring a broader range of new scientific phenomena. Diverse nanoscale materials with specific functionalities, such as exceptional electrical and optical properties, [6][7][8] have been designed or discovered for both academic research and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocarbon species, such as carbon nanotubes, carbon nanofibers, and graphene, have been utilized as functional additives in various application fields. Notably, the physical and chemical properties of these nanocarbon species can be further modulated by doping them with heteroatoms, such as nitrogen and sulfur. In this work, we report an efficient strategy for fabricating ternary-heterostructured N-doped graphene (NG)/WSe 2 –WO 3 (W–W) nanohybrids (NG/W–Ws, where the symbols “/” and “–” denote out-of-plane and in-plane, respectively) as a catalyst for the HER. The physical exfoliation of bulk graphite and WSe 2 together with polyaniline (PANI), which is an exfoliating and N-doping agent, resulted in graphene/PANI/WSe 2 nanohybrids.…”
Section: Introductionmentioning
confidence: 99%